Development the result based management in Disease Prevention and Control Index in the District Level - อ้นอินทร์ ไพรัตน์ (Disease Control Journal, 2014)
This descriptive research aimed to develop Disease Prevention and Control Index in the District Level and to evaluate the result based management in Disease Prevention and Control Index in the District Level. This study was scoped into 2 steps, including (1) To develop the index. : (1.1) study the Result Based Management in Disease Prevention and Control Index in the District Level and the suggestion from the experts were included 6 components to the draft of index; (1.2) the verify and evaluation by seminar form experts. (2) the evaluation of the result based management in Development the Result Based Management in Disease Prevention and Control Index that qualify in this samples such as network, responsible staff both province and district level. The data involved the 182 questionnaire. The results was utilized by selecting the index that indicated the mean score at least 3.51 and standard deviation less than 1. The results revealed that develop Disease Prevention and Control Index in the District Level included 6 components and total 106 indicators. The proper evaluation index were remained 96 indicators and the possible evaluation index also were remained 63 indicators. The priority results indicated that (1) the strategic planning; (2) The leader of the organization; (3) The important clients and streak holders; (4) The process of management; (5) The human resource management; (6) The analysis and knowledge management. Suggestion of this research was appointed criteria of indicators about the result and scoring method for evaluated the result based management in Disease Prevention and Control Index in the District Level.